KIAI SEBAGAI PEMIMPIN TRANSFORMASIONAL DALAM INTEGRASI NILAI PESANTREN PADA SEKOLAH KEJURUAN - Fauziyah, Lilik; Sauqi Futaqi; Zuli Dwi Rahmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the importance of integrating pesantren values into Vocational High School (SMK) education, which tends to be oriented towards work skills and industry needs. In this context, the leadership of the Kiai plays a strategic role in maintaining the balance between vocational education and the development of students' religious character. This study aims to analyze the leadership of the Kiai as a transformational leader in the integration of pesantren values in SMK education at Pondok Pesantren Bustanul Hikmah. The research uses a qualitative approach. Data were obtained through observation, interviews, and documentation involving Kiai, school principals, teachers, and students. Data analysis was carried out through data condensation, data display, and drawing conclusions. The research results indicate that the leadership of Kiai reflects dimensions of transformational leadership, namely idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. The integration of pesantren values is carried out through learning, habituation, and school culture. The exemplary role of Kiai, religious programs, openness to innovation and deliberation, as well as a structured coaching system are important factors in the internalization of pesantren values. This study concludes that the transformational leadership of Kiai plays a significant role in shaping pesantren-based vocational education that can balance students' vocational competence and religious character.